2018
DOI: 10.1016/j.micpath.2018.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of extracted bioactive molecules of Schinus terebinthifolius ripened fruits against some pathogenic bacteria

Abstract: The aim of this work is to identify the chemical constituents and the bioactivity of essential oil (EO), acetone extract (ACE) and n-hexane extract (HexE) of S. terebinthifolius ripened fruits using GC-MS. Total phenolic content and antioxidant activity of extracts were determined using the Folin-Ciocalteu and 1,1-diphenyl-2-picryl-hydrazyl (DPPH) assays, respectively. The toxicity against the growth of Acinetobacter baumannii, Bacillus subtilis, Escherichia coli, Micrococcus flavus, Pseudomonas aeruginosa, Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 40 publications
2
26
0
1
Order By: Relevance
“…The monoterpenic or sesquiterpenic hydrocarbons and their oxygenated derivatives are considered as potential antimicrobial agents by many studies. Thus, these results agree with other previous works [9,18,21,26,75,76].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The monoterpenic or sesquiterpenic hydrocarbons and their oxygenated derivatives are considered as potential antimicrobial agents by many studies. Thus, these results agree with other previous works [9,18,21,26,75,76].…”
Section: Discussionsupporting
confidence: 94%
“…Extracts and EOs, especially from fruits, have been studied extensively in dozens of works, e.g., oleic acid, δ-cadinene, α-phellandrene, 1b,5,5,6α-tetramethyloctahydro-6H-indeno [1,2-b]oxiren-6-one, aromadendrene, hexadecanoic acid-2,3-dihydroxypropyl ester, α-caryophyllene, and germacrene D were the main compounds found in the ethyl ether extract of S. terebinthifolius fruits with good antifungal activity against T. harzianum and A. niger [2]. Acetone extract from ripened fruits with oleic acid, α-phellandrene, and δ-cadinene as main compounds had observed antibacterial activity [26]. Other compounds such as flavonoids, phenols, tannins, anthraquinones, quercetin, kaempferol, biphenyl esters, and steroids were isolated from the fruits of S. terebinthifolius [27][28][29][30][31], with potential antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, EbEO is mainly composed by sesquiterpenes such as δ-cadinene, β-caryophyllene, α-muurolol, α-cadinol, and bicyclogermacrene (Da Silva et al, 2015). The anti-S. aureus activity of EOs containing these sesquiterpenes is well documented in the literature (Mulyaningsih et al, 2010;Salleh et al, 2015;Guerrini et al, 2016;Nishanbaev et al, 2018;Salem et al, 2018). Our results from time-kill studies demonstrated that EbEO is an antibacterial agent showing a synergetic interaction with ampicillin, chloramphenicol, and kanamycin; and additive effects with ciprofloxacin and erythromycin.…”
Section: Discussionsupporting
confidence: 70%
“…Analysis of the EOs was performed using an Agilent 6890 gas chromatograph-mass spectrometer (GC-MS) equipped with an Agilent mass spectrometry detector with a direct capillary interface and HP-5MS fused silica capillary column (30 m × 0.32 mm × 0.25 µm film thickness) (Thermo Scientific, Austin, TX, USA). The program temperature and samples were carried out following previous published works [41,42]. Identification of the constituents was performed based on an mass spectra (MS) library search (National Institute of Standards and Technology (NIST) and Wiley), and by comparing with data in the MS literature [43,44].…”
Section: Gc-ms Analysis Conditionsmentioning
confidence: 99%